The Analysis of Interpersonal Communication in Sport From Mixed Methods Strategy: The Integration of Qualitative-Quantitative Elements Using Systematic Observation - Izquierdo, Conrad; Anguera, M. Teresa (Frontiers in Psychology, 2021)
The objective to which this manuscript is oriented to is focused on the analysis of interpersonal communication in sport. The multimodal essence of human nature adopts special characteristics in individual and team sports, given the roles that athletes adopt in different circumstances, depending on the contingencies that characterize each competition or each training session. The mixed methods framework allows us to advance in the ways of integration between qualitative and quantitative elements, taking advantage of the proven possibilities of systematic observation, which we can consider mixed method in itself, and which provides rigor and flexibility in the study of the communicative flow in sport. Depending on the wide diversity of sports modalities, a wide range of possibilities is proposed, but considering macro-stages that respond to the QUAL-QUAN-QUAL, which is ideal for the study of interactive relationships in very varied contexts, from the field to the pool, or from athletics to football, and contemplating both direct observation situations, characterized by high perceptiveness, and indirect observation situations, the result of verbal behavior or documentary material. In this work we start from a conceptual positioning about interpersonal communication, to later show the sequential gear in sports about obtaining qualitative data, its transformation into other types of data that are still qualitative but have been structured, analyze them quantitatively, and return to a qualitative stage where the interpretation of the results is possible. This process of quantitizing constitutes the cornerstone that gives shape and structure to any research on interpersonal communication in sport that combines the fine nuances of qualitative data (a motor action, a gesture, an exclamation, ...) with the power of robust quantitative data analysis suitable for the treatment of organized qualitative data, which will provide qualitative feed-back.